The Pengaruh Return On Asset, Debt To Equity Ratio Dan Debt To Total Asset Ratio Terhadap Harga Saham Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Iindonesia (BEI) Periode 2016 - 2020 - Ratna Nadia Sari; Nunung Nurhasanah; Sonny Hersona (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of Return On Assets (ROA), Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR) on stock prices. With a population of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This study uses a quantitative approach with descriptive verification method. The sample in this study was determined by purposive sampling technique, so that the sample that met the criteria for taking this sample was 20 companies. The data collection technique in this study uses documentation techniques, with data analysis techniques using Multiple Linear Regression Analysis. The results of this study conclude that partially Return On Assets (ROA) has a negative and insignificant effect on stock prices, Debt to Equity Ratio (DER) has a positive and significant effect on stock prices and Debt to Assets Ratio has a negative but significant effect on stock prices. And simultaneously Return On Assets (ROA), Debt to Equity Ratio (DER) and Debt to Assets Ratio (DAR) to stock prices in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2016 – 2020. Keywords: Return On Asset, Debt to Equity Ratio, Debt to Total Asset Ratio, Stock Price